2017
DOI: 10.1364/ao.56.001730
|View full text |Cite
|
Sign up to set email alerts
|

Automatic low-order aberration correction based on geometrical optics for slab lasers

Abstract: In this paper, we present a method based on geometry optics to simultaneously correct low-order aberrations and reshape the beams of slab lasers. A coaxial optical system with three lenses is adapted. The positions of the three lenses are directly calculated based on the beam parameters detected by wavefront sensors. The initial sizes of the input beams are 1.8  mm×11  mm, and peak-to-valley (PV) values of the wavefront range up to several tens of microns. After automatic correction, the dimensions may reach n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It is found that the peak-to-valley (PV) value of the wavefront is 1.16 µm and the root mean square (RMS) is 0.26 µm after subtracting the defocus and tilt, since these low-order aberrations can be easily corrected by geometric optics. [16] It also can be seen from the measured result that the wavefront distortion is relatively small compared to Ref. [17].…”
Section: Experimental Investigation To the Vcsel Side-pumped Rod Lasermentioning
confidence: 68%
“…It is found that the peak-to-valley (PV) value of the wavefront is 1.16 µm and the root mean square (RMS) is 0.26 µm after subtracting the defocus and tilt, since these low-order aberrations can be easily corrected by geometric optics. [16] It also can be seen from the measured result that the wavefront distortion is relatively small compared to Ref. [17].…”
Section: Experimental Investigation To the Vcsel Side-pumped Rod Lasermentioning
confidence: 68%
“…Adaptive optics (AO) is a technology that can correct the wavefront distortion of the laser beam in real-time, as shown in Figure 1 . It can compensate the dynamic laser beam aberration in real-time, and has been applied in many laser systems with remarkable results [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in 2014, Yang et al from the Institute of Optics and Electronics, Chinese Academy of Sciences, enhanced the beam quality of a solid-state slab laser with an output power of 1.3 kW from 13.1 to 2.3 times the diffraction limit using an AO system without wave-front detection [8]. In 2017, the Institute of Optics and Electronics at the Chinese Academy of Sciences reduced the output beam's PV values of wave-front from 57.26 to 1.87 μm with a loworder aberration autocorrection approach under limitations [9]. In 2018, Yang et al determined the beam quality factor for a 750-MW solid-state slab laser to be 1.64 times the diffraction limit using an AO system combined with the related low-order aberration-correction approach [10].…”
mentioning
confidence: 99%